Analysis of enterprise low-carbon technology innovation via a tripartite evolutionary game under dual supervision - Zhang, Qiwen; Zhao, Dechao; Wang, Jinyuan (Frontiers in Environmental Science, 2025)
IntroductionEnterprise innovation in low-carbon technology is essential for achieving carbon peak and neutrality goals. A thorough understanding of the evolutionary dynamics among the government, financial institutions, and enterprises is key to fostering low‐carbon technology innovation.MethodsThis paper develops an evolutionary game model involving the government, financial institutions, and enterprises engaged in low‐carbon production and uses MATLAB to simulate evolutionarily stable strategies under different conditions. This approach enhances the understanding of stakeholder conflicts in low‐carbon production, strengthens the dual regulatory framework, encourages enterprises to innovate in low‐carbon technologies, and explores the interactions among these stakeholders.ResultsWhen the government implements green economic policies, financial institutions develop innovative green financial products to provide green financial services, enterprises engage in low‐carbon technology innovation, and the system reaches an optimal evolutionary state. Under dual regulation, enterprise income and the initial willingness of the government and financial institutions to participate significantly influence enterprise behavior. The government should regulate enterprises’ operating risk coefficient and the feedback coefficient of low-carbon technology innovation on social welfare, ensuring that they remain within reasonable limits, thus motivating enterprises to pursue low‐carbon innovation and implement low‐carbon production practices. Moderate government incentives and penalties can motivate enterprises to pursue low‐carbon innovations, with subsidies proving more effective than taxes in reducing rent‐seeking behavior that exploits green financial dividends.DiscussionThis study provides effective strategies and insights for promoting low‐carbon technology innovation with stakeholder participation and offers policy recommendations for strengthening the dual regulatory system.